Analysis of Direct Medical Costs for Inpatients with Chronic Obstructive Pulmonary Disease at Jember Lung Hospital - Ayu Putri MS; Devi Rahayu; Shinta Mayasari; Wima Anggitasari (Indonesian Pharmacopeia Journal, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic respiratory disease characterized by progressive airflow limitation. The goals of COPD therapy are to reduce symptoms, decrease exacerbations, improve quality of life, and reduce mortality (Kristiningrum, 2019). Differences in patient characteristic and disease severity may affect therapeutic needs and the costs incurred by patients. Direct medical cost analysis is one of the components of the Cost Of Illness method used to determine the economic burden of a disease (Andayani, 2022). This study aimed to analyze the direct medical costs of hospitalized COPD patients at Jember Lung Hospital. This study was an observational descriptive study with a retrospective design using secondary data from medical records of COPD patients during the January-October 2025 period. The sampling technique used was total sampling with a total sample of 71 patients. Cost analysis was performed using the Cost Of Illness (COI) method. The results showed that COPD patients were predominantly male with 53 patients (74,65%), aged 60-69 years with 32 patients (45,07%), and had a length of stay of 4-6 days with 40 patients (56,33%). The average medication cost was IDR 986.697, treatment cost was IDR 1.394.451, and laboratory cost was IDR 137.242. The average direct medical cost was IDR 2.518.390, which was lower than the INA-CBG’s tariff of IDR 4.888.400. Treatment cost was the largest cost component contributing to the direct medical costs of hospitalized COPD patients. Key words: COPD; direct medical cost; Cost of Illness; pharmacoeconomics; COPD; hospitalization